Sikap dan Perbuatan Terpuji Sebagai Syarat Modifikasi Pidana Mati - Muhammad Firdaus; Mar’ie Mahfudz Harahap (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to explain commendable attitudes and actions or good behavior referred to in law as a condition for modifying the death penalty and aims to understand the concept of commendable attitudes and actions from the perspective of Islamic criminal law. The problem focuses on the commendable attitudes and actions referred to in Article 100 of Law Number 1 of 2023 concerning the Criminal Code. This is ambiguous because the indicators and benchmarks for the commendable attitudes and actions in question have not been clearly regulated so they are very subjective. The writing method uses a normative approach and data collection techniques use library research. This research is descriptive and aims at problem-solution. The results of the research show that the concept of commendable attitudes and actions in Islamic Criminal Law towards death row inmates for the crime of premeditated murder has several indicators, namely: 1. Feeling of regret; 2. Responsible for his actions; 3. There is a desire to repent; 4. Get forgiveness from the victim's family. The achievement of this commendable attitude and action is to obtain forgiveness from the victim and pay compensation to the victim's family. The concepts exemplified by Islamic criminal law should be adapted into positive criminal law to explain the meaning of commendable attitudes and actions in order to achieve justice, certainty and usefulness of the law.